Quantification of Bone Fatty Acid Metabolism and Its Regulation by Adipocyte Lipoprotein Lipase - Bartelt, Alexander (Int J Mol Sci, 2017)
Adipocytes are master regulators of energy homeostasis. Although the contributions of classical brown and white adipose tissue (BAT and WAT, respectively) to glucose and fatty acid metabolism are well characterized, the metabolic role of adipocytes in bone marrow remains largely unclear. Here, we quantify bone fatty acid metabolism and its contribution to systemic nutrient handling in mice. Whereas in parts of the skeleton the specific amount of nutrients taken-up from the circulation was lower than in other metabolically active tissues such as BAT or liver, the overall contribution of the skeleton as a whole organ was remarkable, placing it among the top organs involved in systemic glucose as well as fatty acid clearance. We show that there are considerable site-specific variations in bone marrow fatty acid composition throughout the skeleton and that, especially in the tibia, marrow fatty acid profiles resemble classical BAT and WAT. Using a mouse model lacking lipoprotein lipase (LPL), a master regulator of plasma lipid turnover specifically in adipocytes, we show that impaired fatty acid flux leads to reduced amounts of dietary essential fatty acids while there was a profound increase in de novo produced fatty acids in both bone marrow and cortical bone. Notably, these changes in fatty acid profiles were not associated with any gross skeletal phenotype. These results identify LPL as an important regulator of fatty acid transport to skeletal compartments and demonstrate an intricate functional link between systemic and skeletal fatty acid and glucose metabolism.